Denotative and Connotative Meanings in the Book of Celoteh R.A. Kartini - Sri Utami Rizki; Riri Kumalasari; Octavio Sin Trindade (Jurnal Sastra Indonesia, 2026)
This study examines the denotative and connotative meanings in the book Celoteh R.A. Kartini, which represents a collection of Kartini’s thoughts reflecting women’s experiences during the colonial era. Although Kartini’s ideas have been widely discussed in literary and historical studies, research specifically focusing on the analysis of denotative and connotative meanings in this work remains limited. Therefore, this study aims to identify, analyze, and describe the forms and meanings of denotative and connotative expressions in the text. This research employs a qualitative descriptive method with a semantic approach. Data were collected through close reading and note-taking, and then analyzed using classification and interpretation based on semantic categories. The findings reveal 24 data points, comprising 12 denotative and 12 connotative instances. Denotative meanings tend to convey explicit, literal ideas, while connotative meanings reflect deeper emotional, cultural, and ideological nuances, particularly regarding the oppression and struggles of women in the colonial period. These findings indicate that Kartini’s language is not only informative but also expressive, implicitly conveying criticism of social injustice and gender inequality. The connotative meanings, in particular, strengthen the rhetorical power of Kartini’s expressions in articulating resistance and hope. This study contributes to semantic and literary studies by enriching the analysis of meaning in historical texts and providing insights into how language functions as a medium for expressing women’s voices and social realities.